Bioethics and disaster medicine - Sgreccia, Elio; Fasanella, Giuseppe (Medicina e Morale, 1989)
Man's relationship with the environment has changed over the centuries as technical development has progressed. Indeed, the history of technology represents man's desire to increase his power over nature. But while the application of ever newer technologies has brought about profound transformations in human life, it has also increased the risk of catastrophe.